Penerapan Metode Pieces Pada Sistem Informasi Manajemen WO MAX.ENTERTAINMENT - Baiti Rahman; Muhammad Arifin; Noor Latifah; Diana Laily Fithri (STMIK Budi Darma, 2023)
Wedding Organizer (WO) Maxentertainment is a type of business engaged in the service sector and plays an important role in the success of the reception which is a sacred moment. The application of the PIECES method aims to analyze the feasibility of the system. This analysis is used to make decisions if the system has problems or is not functioning properly. The results of the analysis are used as a basis for improving the system. At the stage of developing this research system using the waterfall method with needs analysis through observation, interviews and literature study. Meanwhile, system design uses the UML (Unified Modeling Language) method. Coding uses the PHP programming language and MySQL database. This research produces an information system that can help manage data and make it easier for customers to place orders. Meanwhile, admins, partners and owners can make it easier to manage their wedding organizers.